2010
DOI: 10.1098/rspb.2010.1641
|View full text |Cite
|
Sign up to set email alerts
|

Decay of vertebrate characters in hagfish and lamprey (Cyclostomata) and the implications for the vertebrate fossil record

Abstract: The timing and sequence of events underlying the origin and early evolution of vertebrates remains poorly understood. The palaeontological evidence should shed light on these issues, but difficulties in interpretation of the non-biomineralized fossil record make this problematic. Here we present an experimental analysis of decay of vertebrate characters based on the extant jawless vertebrates (Lampetra and Myxine). This provides a framework for the interpretation of the anatomy of soft-bodied fossil vertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
159
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(161 citation statements)
references
References 51 publications
1
159
1
Order By: Relevance
“…If only taphonomic alterations occurred in Triazeugacanthus, the smallest specimens would represent the most rotten specimens; accordingly some of these observed structures are among the last elements to decay or to be lost during decomposition of a vertebrate in an aquatic environment [18,19]. These elements are also among the first anatomical structures to form in early ontogeny that have a great potential to be fossilized.…”
Section: Discussionmentioning
confidence: 99%
“…If only taphonomic alterations occurred in Triazeugacanthus, the smallest specimens would represent the most rotten specimens; accordingly some of these observed structures are among the last elements to decay or to be lost during decomposition of a vertebrate in an aquatic environment [18,19]. These elements are also among the first anatomical structures to form in early ontogeny that have a great potential to be fossilized.…”
Section: Discussionmentioning
confidence: 99%
“…[51,55] Decay in seawater has now been monitored in a range of taxa in laboratory experiments (see Table S1, Supporting Information): anthozoans, [56] annelids, [48] chaetognaths, [57] priapulids, [18] onychophorans, [17] pterobranchs, [58] enteropneusts, [59] nonvertebrate chordates, [20] and cyclostomes. [60] Thus the sequence of character loss has been determined for taxa representing most clades of eumetazoans. Despite the diversity of body plans analyzed in these experiments, collectively they show that different tissues decay at different rates, with some common patterns of susceptibility to decay across different organisms, and that different character systems are lost at different stages in the decay process.…”
Section: Boxmentioning
confidence: 99%
“…Experiments on cyclostomes and invertebrate chordates [20,60] showed that the notochord persists until the latest stages of decay ( Figure 4). Nonetheless, the notochord is apparently absent in several taxa from Mazon Creek [63] even though other characters indicate that they belong to the vertebrate crown group, and therefore, possessed a notochord.…”
Section: Some Decay Resistant Features Do Not Preserve In Exceptionalmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Eyes in basal vertebrates are relatively decay resistant 18,19 and pigment is one of the most decay resistant features in lampreys 18,19 . In Tullimonstrum, the dark structures are paired, bilaterally disposed and comprise thick, multi-layered masses of melanosomes.…”
mentioning
confidence: 99%